Characteristics and Behavior of Managers towards Cost Consciouness (Empirical studies on Leadership Working Units in Southern Kalimantan Provincial Government) - Ade Adriani; Norlena Norlena (Journal of Wetlands Environmental Management, 2014)
The research’s purpose is to test empirically examine the effect of the regional financial accounting information system characteristics and behavior of managers towards cost consciouness in the use of financial information systems area. Manager behavior is proxied by the control decision-making and cost management consciousness as practiced by Abernethy and Emidia. The study will examine whether the phenomenon occurs in Indonesia, particularly in the South Kalimantan provincial government. Concretely influences the characteristics of accounting information systems in this area of financial information systems, it is seen from the behavior of Chief SKPD in the South Kalimantan provincial government in decision-. The Result shows that Characteristics of Financial Accounting Information Systems affect the use of the local financial system to control decision-making and management. There is a significant relationship between system characteristics financial information to the control area decisions. Financial regionally accounting information system characteristics were positively associated with decision controlling policy. The use of financial information systems area for menajament decisions affect cost consciousness. The effect of control decisions the cost consciousness is significant.